If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -5 = -1y + 15 Reorder the terms: -5 + 4y = -1y + 15 Reorder the terms: -5 + 4y = 15 + -1y Solving -5 + 4y = 15 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -5 + 4y + y = 15 + -1y + y Combine like terms: 4y + y = 5y -5 + 5y = 15 + -1y + y Combine like terms: -1y + y = 0 -5 + 5y = 15 + 0 -5 + 5y = 15 Add '5' to each side of the equation. -5 + 5 + 5y = 15 + 5 Combine like terms: -5 + 5 = 0 0 + 5y = 15 + 5 5y = 15 + 5 Combine like terms: 15 + 5 = 20 5y = 20 Divide each side by '5'. y = 4 Simplifying y = 4
| 2(y-5)-2=4y | | 3(5x)=5x+5 | | f(x)=x^4-11x^3+60x^2-396x+864 | | (360-x)-x= | | 9x-9=x-8 | | 17=-3(23-b)+2(b-2) | | 17=3(23-b)+2(b-2) | | 4x+7=108 | | x(3x^2+6x+-1)+4x= | | x(3x^2+6x+-1)+4x=0 | | F(x)=-x^2-80x-1800 | | 8x+14y= | | x^3=1500 | | 28z^2+28z+15= | | x+3/6=x+1/4 | | X^2+10+13-4=0 | | 50+2x-4=100 | | 59=35-4(x-2) | | 5x-8x+15=2x+30 | | 8x-(6x+3)=4x-21 | | (3w+7)(1-w)=0 | | 5=x+25 | | (3w+7)(1+w)=0 | | 4x-5=28-2x | | 1.6y+y=5421 | | f(x)=9x+9x^2 | | 12-2x=2x | | 5n-15=2n+12 | | 4x-5=29-2x | | (-6)x+1=216 | | (.6)x+1=216 | | (4y-5)(3-y)=0 |